Transcriptome-Wide Identification of Neuropeptides and Neuropeptide Receptors in the Twenty-Eight-Spotted Ladybird Henosepilachna vigintioctopunctata - Quanxing Lei; Ziming Wang; Shuangyan Yao; Aili Lin; Yunhui Zhang; Chengxian Sun; Xiaoguang Liu; Mengfang Du; Xiaoming Liu; Shiheng An (Insects, 2025)
The ladybird beetle, Henosepilachna vigintioctopunctata, is an oligophagous pest with significant economic impact. This pest causes considerable economic damage on numerous Solanaceae crops. Neuropeptides, along with their designated receptors, play a pivotal role in regulating diverse biological processes in insects, presenting a promising avenue for innovative pest management strategies. Herein, the transcriptome of the central nervous system (CNS) of H. vigintioctopunctata was sequenced. Overall, our analysis identified 58 neuropeptide precursor genes, from which 98 diverse mature peptides were predicted. Furthermore, 31 neuropeptide receptor genes belonging to three distinct classes were discovered, along with predictions for their potential ligands. Moreover, the expression patterns of these 58 neuropeptide genes across larval brain tissue, ventral nerve cord, and gut were evaluated using quantitative real-time PCR. Collectively, these findings will significantly contribute to future research focused on understanding the physiological functions and pharmacological characteristics of neuropeptides and their receptors in H. vigintioctopunctata. Ultimately, these insights may facilitate the development of targeted neuropeptide-based solutions for managing this pest affecting solanaceous plants.